Prevalence of phantom pain in amputees: a systematic literature review - Probstner, Danièlle (2006)
Introduction: Phantom sensation, painful or not, is usually present in the follow-up of subjects with an amputee. Phantom pain reduces the quality of life of patients, whom make heavy use of medical system. Because of this, the prevalence of phantom limb pain has an important role not only in the follow up of amputees, but in the management of medical system. Objectives: Systematic review of literature about phantom pain in amputees, taking into account oncologic pacients. Method: It was done a search at Internet data basis Pubmed and Lilacs from 2000/01/01 to 2005/12/31, looking for prevalence of phantom limb pain in amputees. It was also used the related article trick, available at Pubmed. Results: It was identified 11 studies related to prevalence, none of them were exclusively about oncologic patients. It was found a prevalence of phantom pain between 26% and 80%. It was not found Latin Americans studies about prevalence of phantom limb pain in amputees. Conclusions: There were few studies about this theme in the last five years with a lack of Latin American data. Moreover, it was not found exclusive studies about oncologic patients, making possible future researches about phantom pain and its peculiarities in this kind of etiology.